THE ROLE OF MADRASAH PRINCIPAL LEADERSHIP IN TECHNOLOGY-BASED EDUCATIONAL INNOVATION - Taskya Nafsi Al Husna; Nur Hidayati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to describe the role of the madrasah principal’s leadership in encouraging technology-based educational innovation, as well as to describe the strategies employed by the principal in utilizing technology to improve the quality of education. The research adopts a qualitative approach, which involves investigating phenomena in their natural settings and employs a descriptive research design. The selection of informants was carried out using the snowball sampling technique, beginning with initial informants and subsequently expanding by seeking recommendations for additional informants relevant to the research focus. Data collection techniques included observation, interviews, and documentation. The data analysis procedures consisted of data reduction, data presentation, and conclusion drawing al well as SWOT. The results of the study indicate that the madrasah principal plays a role as an initiator of digital learning programs. This includes innovations implemented in the madrasah, such as the use of platforms like Google Classroom, Madrasah e learning, the Madrasah SIM Dashboard, the use of videos in instructional methods, and online evaluation. The principal’s role is not limited to structural leadership; the principal also serves as a role model in the use of technology, both in management practices and academic supervision. This strategy not only demonstrates the principal’s commitment to developing educational innovation but also reflects systematic, participatory, and adaptive planning in response to the dynamics of 21st-century education. This study contributes to the development of research in educational management and leadership, particularly within the context of madrasah.